Kendala dan Strategi dalam Meningkatkan Perekonomian Nelayan Melalui Hasil Tangkapan Laut di Kelurahan Belawan Bahari - Ahyana Isma; Irfan Ruhaimi; Mahdariani Mahdariani (Pusat Riset dan Inovasi Nasional, 2024)
Abstract. Belawan Bahari Village is one of the sub-districts in Belawan where local people use the water area for fishing or fishing activities. The problem raised in this study is regarding the constraints experienced by the fishermen as well as regarding the strategies undertaken to improve the fishermen's economy from marine catches in the Belawan Bahari Village. This research was conducted using a qualitative approach with the type of research case study research (case study) and is descriptive in nature. The method used in this research is through interviews, observation, and documentation. The results showed that fishermen still depend on tauke due to the constraints experienced by fishermen in meeting their economic needs, such as fishermen still lacking access to capital for fishing operational costs, fuel prices that have increased, lack of knowledge regarding the use of income for business development, and conditions nature that affects the state of the sea. In cooperating with the tekong/tauke/ship owners the income is divided, known as a profit sharing system, which also affects the economic life of fishermen, especially the income earned by fishermen. to reduce these constraints several strategies can be carried out as efforts or solutions, namely in the form of activities in the form of outreach or an extension for business development for fishermen's wives so that they can optimize marine catches, assistance from the government in the form of provisions such as facilities and infrastructure in catching marine products, providing direct subsidies in the form of reducing fuel prices, as well as support and monitoring from various parties, in order to improve the welfare of fishermen.